Kajian ke atas kaedah pengalaman pendedahan pelaporan penyata aliran jurnal Malaysia - Ali Khan, Mohd. Noor Azli; Abdul Rahim, Kamaruzzaman (Universiti Teknologi Malaysia, 2004)

(untitled)
This study is an extension research for discusses the practice of cash flow statements reporting disclosure of finance companies listed on the main board of the Kuala Lumpur Stock Exchange (KLSE). Random sampling technique was used in this study. Out of 598 companies, 181 companies were selected for the period ended 31st December 2003 from various industries. An annual report was used for analysing the practice of the KLSE listed companies. This study examined the practice of method in reporting its cash flows from operating activities and the practice of classified of interest, dividend and income taxes in financial statements. Furthermore, this statistical analysis also showed that there wasn’t a significant relationship between method of reporting cash flows from operating activities with type of industry, the size of company and audit firm.